Density functional studies of fused dodecahedral and irregular-dodecahedral water cages12. Issue 91 (9th October 2015) - Shilpi, V.; Kaur, Surinder Pal; Ramachandran, C. N.
<x xml:space="preserve">Abstract</x> The fused cages of dodecahedral and irregular-dodecahedral water cages with the maximum number of t1d hydrogen bonds were studied using the dispersion corrected density functional method.